Embarazo adolescente durante la pandemia de COVID-19 en Babahoyo (2020-2022). - Moreira Jurado, Ariana Celena (2024)
In the following research, surveys were conducted among students of the schools Técnico Emigdio Esparza Moreno and Réplica Eugenio Espejo Babahoyo , pregnant adolescents belonging to the province of Los Ríos in the Babahoyo canton, the current situation in which the lives of adolescents are developing in relation to early pregnancy; implies entering into a problem that involves multiple causes, which entails a social, economic and cultural impact, due to the links between poverty, exclusion and early fertility. Adolescent pregnancy can lead adolescents to drop out of school, which can have long-term negative consequences on their education and job opportunities, the stages of adolescence, which include puberty, early, middle and late adolescence, The stages of adolescence, including puberty, early, middle and late adolescence, are important to understand the specific needs and challenges of adolescents during the COVID-19 pandemic due to the closure of public institutions, some of which were referred to health centers for delivery care, reduced obstetric care, leading to an increase in the occurrence of risk factors, which can lead to a higher mortality rate. It is important that education and health authorities work together to prevent teenage pregnancy and ensure that pregnant adolescents have access to health services and support to continue their studies. The prevention of adolescent pregnancy and early marriages should address not only medical and sexual and reproductive health aspects, but also the social, cultural and economic factors that contribute to these phenomena. Key words: pregnancy, teenage pregnancy, early marriage, Covid-19, socioeconomic, school dropout.